Dapatkah Good Corporate Governance Mencegah Penghindaran Pajak? - Tarisma Indri Ardianti; Cahyani Nuswandari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
ABSTRACT This study was conducted to examine the influence of audit quality, audit committee, independent commisioners, and institutional ownership on tax avoidance. A quantitive research method was employed. The research population consisted of 238 data points. The sampling technique used was purposive sampling, resulting in 188 data points that met the criteria. Outliers were identified, and 27 data points were removed, leaving 161 data points for testing. Data analysis techniques used in this research included descriptive statistics, classical assumption test, multiple linear regression analysis, model testing, and hypothesis testing. The result of the study that audit quality has a significant positive impact on tax avoidance, independent commissioners have a significant negative impact on tax avoidance, while the audit committee and institutional ownership do not have an impact on tax avoidance. Keywords : Audit Quality, Audit Committee, Independent Commisioners, Institutional Ownership, Tax Avoidance